R. A. M. STERN, J. STAMP (eds.) - Pedagogy and Place: 100 years of architecture education at Yale - Sentieri Omarrementería, Carla (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Robert A. M. Stern and Jimmy Stamp (eds.)Pedagogy and Place: 100 years of architecture education at YaleYale: Yale University Press, 2016, 654 pages. Hardcover. Language: English. $65.00.ISBN-13: 978-0300211924; ISBN-10: 9780300211924